(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
The following text synthesizes some reflections and challenges around university extension during the pandemic based on the experience developed during the years 2020 and 2021 from the Training and Strengthening Program for Community Organizations, extension policy of the Faculty of Social Sciences of the UBA that is turning 20 years old. Our first reaction, with the arrival of the pandemic, was to maintain the links between community organizations, teachers, students, graduates, and workers who are part of the Program, to keep the heart of our community beating. On the other hand, based on the need to think about popular education at a distance, we began to experiment with other languages, both for training spaces and for the processes of collective production of knowledge: photography, collage, music and radio. In this sense, it is not just a question of finetuning listening from the University, but also of thinking of alternative ways of transmitting the knowledge built in products that bring together and highlight diversity, problematizing the centrality of the written word and the traditional idea of the book.